P0016 Exploring DPP4 in intestinal inflammation: a cross-matrix approach using the TNBS-induced model of colitis - S F Gomes; M Ferreira-Duarte; P Dias-Pereira; J Couto; M Duarte-Araújo; M Morato; F Magro (Journal of Crohn’s and Colitis, 2026)
Abstract Background Inflammatory Bowel Disease is an increasingly prevalent chronic intestinal disorder1. Biomarkers of disease are still an unmet need. Dipeptidyl peptidase 4 (DPP4), a membrane enzyme with immunoregulatory roles, can be shed into biological fluids2, but research as a potential biomarker of disease is scarce. This study evaluated DPP4 levels in the serum, colon and feces of rats with and without colitis. Methods This study was approved by institutional/national welfare bodies. Male Wistar Han rats (10–12 weeks) were randomly assigned to control (n = 10) or TNBS-induced colitis (n = 10) groups. Following 8h fasting with 5% sucrose ad libitum, TNBS rats received a rectal instillation of TNBS (18 mg/rat, 250 µL of 21% ethanol) under isoflurane anesthesia. Tramadol (20 mg/kg, PO) and paracetamol (500 mg/kg, PO) were administered daily for analgesia, while metoclopramide (1 mg/kg, PO) was given from day−1 to day2 to enhance intestinal motility. On day7, animals were euthanized, and serum, proximal and distal colon (PC, DC), intestinal content and cage fecal pellets (CFP) were collected. Colitis severity was assessed by macroscopic and microscopic scores. CFP from germ-free and DPP4 knockout (KO) mice and corresponding controls were also analysed. DPP4 was quantified by ELISA, and its localization was evaluated by immunohistochemistry (IHC). Statistical analyses were performed in GraphPad Prism and p<0.05 was considered statistically significant. Results TNBS-treated rats displayed increased macro and microscopic damage, especially in the DC. In controls, DC-DPP4 concentration was lower than PC-DPP4, a difference abolished in TNBS-induced rats (Fig.1A). Serum DPP4 was similar between groups (Fig.1B). In TNBS rats, fecal DPP4 (fDPP4) concentration increased from the PC to the DC and CFP (Fig.1C), and was higher in CFP compared to controls, showing an increase on day5 and 7 (Fig.1D). In controls, IHC revealed DPP4 expression in epithelial, endothelial, and neural cells, being stronger in DC than PC. In TNBS-induced rats, DPP4 remained detectable in epithelial cells near lesions and in inflammatory infiltrates. In the DC of TNBS-induced rats, fDPP4 correlated with tissue DPP4 (r = 0.733, p=0.02), macro (r = 0.872, p=0.009) and microscopic scores (r = 0.771, p=0.032). fDPP4 was reduced in germ-free and DPP4-KO mice compared to their respective controls (Fig.2). Conclusion DPP4 levels are altered during intestinal inflammation. Correlations between fecal and colonic DPP4 support its potential as a biomarker of mucosal changes rather than systemic response. Preliminary data from germ-free and KO mice suggest contributions from epithelial shedding and microbial activity in fDPP4 levels that need to be explored. References: 1.Solitano V, Bernstein CN, Dotan I, et al. Shaping the future of inflammatory bowel disease: a global research agenda for better management and public health response. Nat Rev Gastroenterol Hepatol. Jun 2025;22(6):438-452. doi:10.1038/s41575-025-01063-x 2.Pechmann LM, Pinheiro FI, Andrade VFC, Moreira CA. The multiple actions of dipeptidyl peptidase 4 (DPP-4) and its pharmacological inhibition on bone metabolism: a review. Diabetol Metab Syndr. Jul 25 2024;16(1):175. doi:10.1186/s13098-024-01412-x Conflict of interest: Gomes, Sandra F.: I have no conflict of interests to declare. Ferreira-Duarte, Mariana: I have no conflict of interests to declare. Dias-Pereira, Patrícia: I do not have any conflict of interests to declare. Couto, Joana: I declare that I have no conflicts of interest related to this research. Duarte-Araújo, Margarida: I have no conflict of interests to declare. Morato, Manuela: I have no conflict of interests to declare. Magro, Fernando: Fernando Magro served as speaker and received honoraria from Abbvie, Arena, Biogen, Bristol-Myers Squibb, Falk, Ferring, Hospira, Janssen, Laboratórios Vitoria, Pfizer, Lilly, Merck Sharp & Dohme, Sandoz, Takeda, UCB, Vifor.